“Waste management go to school” program and its relationship with students’ environmental information literacy - Winoto, Yunus; Septian, Falih Ijlal; Shuhidan, Shamila Mohamed (Journal of Environment and Sustainability Education, 2025)
This research looks at how the “Waste Management Go to School” program impacts students’ environmental information education. The study took place in schools involved with the environmental education effort run by the Bening Saguling Foundation in West Bandung Regency, Indonesia. Through simple random sampling, 370 students were selected using a quantitative approach. Questionnaires were used to collect information which was then analyzed with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The researchers looked at three main parts of communication: the person speaking, the message and the channel for delivering the message. The results indicate that knowledge, awareness and attitudes, as well as skills, were all significant factors in student environmental information literacy. Having credible sources was found to be fairly important in helping students become more literate about the environment, according to the communicator variable. Media reports suggested that the right media can increase how interested and knowledgable students are about environmental matters. Also, the message part was found to matter most, pointing out that educational content should be both clear and involve the students. The results indicate that giving priority to strategic communication in schools should help enhance students’ environmental literacy. Research conducted here aids institutions in adopting better ways to teach environmental issues and serves as a reference for introducing sustainability into the curriculum at schools.